2013
DOI: 10.3945/jn.112.170894
|View full text |Cite
|
Sign up to set email alerts
|

Age, Dietary Fiber, Breath Methane, and Fecal Short Chain Fatty Acids Are Interrelated in Archaea-Positive Humans1–3

Abstract: Recent attention has focused on the significance of colonic Archaea in human health and energy metabolism. The main objectives of this study were to determine the associations among the number of fecal Archaea, body mass index (BMI), fecal short chain fatty acid (SCFA) concentrations, and dietary intakes of healthy humans. We collected demographic information, 3-d diet records, and breath and fecal samples from 95 healthy participants who were divided into 2 groups: detectable Archaea (>10(6) copies/g; Arch+ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 52 publications
5
41
1
Order By: Relevance
“…In humans, methanogenic archaea are increased in obese vs lean individuals [68], and intestinal methane production in obese individuals is associated with a higher BMI [69]. However, this association cannot be generalised to all archaea [70], and their relationship with glycaemia has not been reported.…”
Section: Dysbiosis Related To Type 2 Diabetes and Hyperglycaemiamentioning
confidence: 93%
“…In humans, methanogenic archaea are increased in obese vs lean individuals [68], and intestinal methane production in obese individuals is associated with a higher BMI [69]. However, this association cannot be generalised to all archaea [70], and their relationship with glycaemia has not been reported.…”
Section: Dysbiosis Related To Type 2 Diabetes and Hyperglycaemiamentioning
confidence: 93%
“…The relative proportions and activity of methanogens:SRB have long been of interest but mainly in relation to explaining H 2 disposal (103) . Interestingly, Fernandes et al (104) have recently confirmed that methane production and carriage of detectable Archaea (mainly methanogens in human subjects) are inversely related to BMI and that methanogenesis appears to allow more efficient production and absorption of SCFA from dietary fibre fermentation. While the ecological processes regulating the relative abundance of gut SRB and methanogens are not fully understood, ingestion of fermentable fibre increases methanogenesis in CH 4 -producing subjects, while sulphate or dietary protein appear to stimulate the numbers of SRB and presumably their metabolic activities within the gut microbiota (105)(106)(107)(108)(109) .…”
Section: Diet Can Bring Out the Worst Of Microbial Behaviours: Microbmentioning
confidence: 97%
“…It also provides clues about the prevalence and abundance of methanogenic archaea, and among them, Methanobrevibacter smithii, the most important one, is increased in elderly people. [43][44][45] They are described as being correlated with an increase of transit time and inversely correlated to sulfate reducing bacteria. 12 Here, the initial stool from a healthy adult was chosen without methanogens, which was confirmed by the absence of CH 4 in the gas produced by any reactor.…”
Section: Discussionmentioning
confidence: 99%